2002
DOI: 10.1080/gas.37.7.818.824
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease A Positive Response to Infliximab in Crohn Disease: Association with a Higher Systemic Inflammation Before Treatment But Not With -308 TNF Gene Polymorphism

Abstract: A positive clinical response to infliximab was associated with a higher CRP level before treatment in our population of Crohn disease patients, but there was no relevant association with -308 TNF gene polymorphism. We therefore suggest that CRP level may help to identify better candidates for infliximab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(93 citation statements)
references
References 28 publications
2
89
1
1
Order By: Relevance
“…In a Belgian study, in 153 patients treated with infliximab, a baseline CRP .5 mg/l before the start of therapy was associated with a higher response (76%) compared with patients with CRP ,5 mg/l (46%) (p = 0.004). 53 Very similar results have been demonstrated for the humanised anti-TNF molecules CDP-571 and CDP-870, and for the fully human anti-TNF antibodies adalimumab and antiadhesion molecule strategies. [54][55][56] Along the same lines, low or normal baseline CRP values have been associated with a high placebo response and remission rate in clinical trials.…”
Section: Use Of Laboratory Markers To Monitor Disease Activity In Ibdmentioning
confidence: 52%
“…In a Belgian study, in 153 patients treated with infliximab, a baseline CRP .5 mg/l before the start of therapy was associated with a higher response (76%) compared with patients with CRP ,5 mg/l (46%) (p = 0.004). 53 Very similar results have been demonstrated for the humanised anti-TNF molecules CDP-571 and CDP-870, and for the fully human anti-TNF antibodies adalimumab and antiadhesion molecule strategies. [54][55][56] Along the same lines, low or normal baseline CRP values have been associated with a high placebo response and remission rate in clinical trials.…”
Section: Use Of Laboratory Markers To Monitor Disease Activity In Ibdmentioning
confidence: 52%
“…The issue has been further discussed by Vermeire and co-workers as CRP is well studied and shown to correlate with disease activity in CD [13]. Increased CRP levels have been suggested to be associated with better response rates in infliximab treatment [14,15]. In the present study we attempted to optimize the utility of CRP by correlating hs-CRP to disease activity and other biomarkers.…”
Section: Discussionmentioning
confidence: 83%
“…Aside from imaging, many laboratory data are available regarding predictors of response for short- and long-term clinical benefit during therapy with biological agents [15,16,17]. Survival analysis demonstrated that patients in whom CRP levels normalized early (after 4 weeks of a 10-week period) had better long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis demonstrated that patients in whom CRP levels normalized early (after 4 weeks of a 10-week period) had better long-term outcomes. The CRP level at the time of endoscopy significantly correlated with the degree of mucosal healing [16,17]. The positive predictive value of 51.8% for continuing remission at 54 weeks means that a clinician could predict a 1-year response in a patient.…”
Section: Discussionmentioning
confidence: 99%